2007
DOI: 10.1371/journal.pmed.0040341
|View full text |Cite
|
Sign up to set email alerts
|

The Consumption of Khat and Other Drugs in Somali Combatants: A Cross-Sectional Study

Abstract: BackgroundFor more than a decade, most parts of Somalia have not been under the control of any type of government. This “failure of state” is complete in the central and southern regions and most apparent in Mogadishu, which had been for a long period in the hands of warlords deploying their private militias in a battle for resources. In contrast, the northern part of Somalia has had relatively stable control under regional administrations, which are, however, not internationally recognized. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 42 publications
1
67
0
Order By: Relevance
“…A survey conducted in a rural community in southern Ethiopia establishes a prevalence of 50% (Alem et al, 1999). In addition, study conducted in Somalia reported that approximately 36.4% of the respondents had chewed Khat in the week preceding the interview (Odenwald et al, 2007). The difference may be stimulated by studies were conducted many years back, rules and regulation enforcement differences.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in a rural community in southern Ethiopia establishes a prevalence of 50% (Alem et al, 1999). In addition, study conducted in Somalia reported that approximately 36.4% of the respondents had chewed Khat in the week preceding the interview (Odenwald et al, 2007). The difference may be stimulated by studies were conducted many years back, rules and regulation enforcement differences.…”
Section: Discussionmentioning
confidence: 99%
“…The strong relationship between posttraumatic symptoms and health have been described elsewhere (Green & Schnurr, 2000;Schnurr & Green, 2003), including among Somali refugees (Bhui et al, 2003) and Somaliland excombatants (Odenwald et al, 2007b). We did not find any significant relationships between PTSD symptomatology and physical health variables (health complaints and frequency of health service utilization).…”
Section: Discussionmentioning
confidence: 67%
“…Participants reported their history of health problems using a fixed list of common health complaints defined by a previous survey conducted in Somalia (Odenwald et al, 2007a(Odenwald et al, , 2007b. Information regarding access to health services included number of health-related clinical visits and obstacles to accessing health service.…”
Section: Methodsmentioning
confidence: 99%
“…3 There is a growing consensus that mental health care interventions in post con£ict settings need to be integrated into existing systems (Pe¤ rez-Sales et al, 2011) and that the treatment of mental disorders within the health care systems needs to be accompanied by a community based approach that focuses on psychosocial problems (De Jong & Kleber, 2007;Ventevogel et al, 2012). 4 Our group did research on the general adaptation of children (Catani et al, 2010), family violence and child maltreatment Catani, 2009;Catani et al, 2010), inter-partner violence (Saile et al, 2013), and drug-induced psychosis (Odenwald et al, 2005;Odenwald et al, 2007;Odenwald et al, 2009). 5 Mundt et al (2014) state that there is only one review of NET.…”
Section: Resultsmentioning
confidence: 99%